2002
DOI: 10.1111/j.1095-8649.2002.tb02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Rule of age and size at maturity: individual variation in the maturation history of resident white‐spotted charr

Abstract: Individual growth and maturation histories, age, and size at maturity of resident white-spotted charr Salvelinus leucomaenis were examined in a tag-recapture study in a natural river over 3 years. Slow-growing fish reached sexual maturity not only at an older age, but also at a smaller size than fast-growing fish, although females had a larger threshold size at maturity than males at each age. It is suggested that these patterns result from adaptive phenotypic plasticity that depends on individual growth condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…The direction of the changes between the two periods is consistent with the model of Stearns (1992), which predicted that reductions in growth will lead to maturity occurring at a smaller size and older age (see also Chen and Mello, 1999;Morgan and Colbourne, 1999). This finding is also consistent with the results of a three year tagrecapture study, which demonstrated that the slower-growing residents of the white spotted charr Salvelinus leucomaenis reached maturity at a smaller size but older age than faster-growing individuals, a feature considered to reflect adaptive phenotypic plasticity (Morita and Morita, 2002). For A. butcheri, the changes in both the length and age at maturity were pronounced and developed within a relatively short period, highlighting the plasticity of the biological characteristics of this species and thus its ability to respond to the effects of environmental change.…”
Section: Length and Age At Maturitysupporting
confidence: 90%
See 1 more Smart Citation
“…The direction of the changes between the two periods is consistent with the model of Stearns (1992), which predicted that reductions in growth will lead to maturity occurring at a smaller size and older age (see also Chen and Mello, 1999;Morgan and Colbourne, 1999). This finding is also consistent with the results of a three year tagrecapture study, which demonstrated that the slower-growing residents of the white spotted charr Salvelinus leucomaenis reached maturity at a smaller size but older age than faster-growing individuals, a feature considered to reflect adaptive phenotypic plasticity (Morita and Morita, 2002). For A. butcheri, the changes in both the length and age at maturity were pronounced and developed within a relatively short period, highlighting the plasticity of the biological characteristics of this species and thus its ability to respond to the effects of environmental change.…”
Section: Length and Age At Maturitysupporting
confidence: 90%
“…Morita and Fukuwaka, 2007;Stahl and Kruse, 2008). In many cases, such reductions in growth were accompanied by a decline in the length at maturity (Morita and Morita, 2002;Morita and Fukuwaka, 2007) and an increase in the age at maturity, which is consistent with, for example, the model of Stearns (1992) in which such trends represented a balance between reducing fecundity and increasing mortality. Certain studies support this model (Helle and Hoffman, 1998;Morita and Morita, 2002;Grover, 2005;Morita and Fukuwaka, 2007), but none has determined quantitatively, and in a composite manner, the declines in the growth of a species in an estuary as that system became degraded and the reductions in body condition and changes in maturation schedules that accompanied that deterioration.…”
Section: Introductionsupporting
confidence: 84%
“…The differences between the values of length at first gonadal maturation for one species in different seasons might be mainly associated with the geographical location of the studied populations. This phenomenon has already been observed in other species such as Micropogonias furnieri (Vazzoler 1991), Salvelinus leucomaenis (Morita and Morita 2002) and Microstomus pacificus (Abookire and Macewicz 2003).…”
Section: Discussionsupporting
confidence: 66%
“…Variations in length at first gonadal maturation (L 50 ), spawning season, sexual proportion, oocyte development, and fecundity have been described as reproductive tactics with a high level of variability and are important for the success of a generation or cohort resulting from spawning (Frank and Leggett 1994;Vazzoler 1996;Morita and Morita 2002). These tactics have spatial and temporal intraspecific variations related mainly to abiotic and biotic conditions prevailing in the area occupied or in the period when the population was subject to those conditions (Vazzoler 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding and growth are important characteristics of fish life history, which often affects many fitness traits including vulnerability to predation, competitive ability, and fecundity (Arendt 1997;Billerbeck et al 2001;Lankford et al 2001;Morita and Morita 2002). The differences in feeding and growth performances between C. pellegrini and C. carpio were compared in this experiment, and the reason of the displacement of C. pellegrini by C. carpio was analyzed based on physiological characteristics.…”
Section: Introductionmentioning
confidence: 99%